CHLORPYRIFOS SUPPRESSES FEMALE REPRODUCTIVE FUNCTION IN RAT. - KAMALESH DAS; KAUSHIK SARKAR; PANCHALI TARAFDER; PARTHA P. NATH; GOUTAM PAUL (International Journal of Pharma and Bio Sciences, 2014)
We report here the toxic effects of chlorpyrifos, a broad-spectrum organophosphorous insecticide, on female reproductive function in rat model. We observed significant alterations in the rhythmicity and phasic cellular characteristics of estrous cycle with a concomitant increase in diestrus index in chlorpyrifos treated female rats in a dose-dependent manner (5.4 and 8.1 mg/Kg.b.wt./day) compared to control rats. The levels of serum female reproductive hormones (LH, FSH and estradiol) were also decreased dose-dependently. Structural disorders and degenerations of ovarian and uterine tissues were observed in treated rats. The mean body weight and organ weight of ovary and uterus in treated female rats were also significantly decreased. From the results, we may conclude that chlorpyrifos suppresses the female reproductive functions in rat presumably by impairing the estrous cycle function and inducing oxidative stress induced structural disorders and depletions of ovarian and uterine tissues.